2013
DOI: 10.1371/journal.pone.0074808
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of Koalas with a Recombinant Chlamydia pecorum Major Outer Membrane Protein Induces Antibodies of Different Specificity Compared to Those Following a Natural Live Infection

Abstract: Chlamydial infection in koalas is common across the east coast of Australia and causes significant morbidity, infertility and mortality. An effective vaccine to prevent the adverse consequences of chlamydial infections in koalas (particularly blindness and infertility in females) would provide an important management tool to prevent further population decline of this species. An important step towards developing a vaccine in koalas is to understand the host immune response to chlamydial infection. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Positive control sera against the KoRV-A recombinant viral proteins were generated in goats (serum 33 against rp27Gag, serum 31 and 46 against rp15E, serum 61 against gp70/rp52) (Fiebig et al, 2006;Denner, 2014). As secondary antibodies, an anti-goat antiserum (Dako, polyclonal rabbit antibodies, peroxidase conjugated), and a combination of a sheep anti-koala antiserum (Kollipara et al, 2013) and an anti-sheep antiserum (Biomol, Rockland, donkey anti-sheep IgG, peroxidase conjugated) were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Positive control sera against the KoRV-A recombinant viral proteins were generated in goats (serum 33 against rp27Gag, serum 31 and 46 against rp15E, serum 61 against gp70/rp52) (Fiebig et al, 2006;Denner, 2014). As secondary antibodies, an anti-goat antiserum (Dako, polyclonal rabbit antibodies, peroxidase conjugated), and a combination of a sheep anti-koala antiserum (Kollipara et al, 2013) and an anti-sheep antiserum (Biomol, Rockland, donkey anti-sheep IgG, peroxidase conjugated) were used.…”
mentioning
confidence: 99%
“…It is interesting that those animals carrying KoRV-A and also infected with exogenous KoRV-B also failed to produce antibodies against KoRV-A, although it is unclear whether they had antibodies against the receptor-binding site of KoRV-B gp70, the only sequence different from that of KoRV-A. To demonstrate the functionality of the secondary antibody, a combination of sheep anti-koala and donkey anti-sheep antibodies, sera from animals infected with chlamydia or immunised with the recombinant major outer membrane protein (MOMP) of chlamydia were shown to react in a Western blot analysis against MOMP (Kollipara et al, 2013). Furthermore, the combination of the sheep anti-koala and the anti-sheep antibodies reacted with purified koala immunoglobulins in a Western blot assay (Fig.…”
mentioning
confidence: 99%
“…Our previous koala and sheep vaccine studies also give us the opportunity to identify potential peptide antigens that were recognised independently of the species studied. When the MOMP-G vaccine-induced epitope response in lambs was compared with that of koalas vaccinated with MOMP-G from our previous vaccine trial [ 29 ], we found that epitope presentation was more diverse (15 epitopes) in lambs in comparison to koalas (4 epitopes). Two peptides from the conserved domain and variable domains 3 in vaccinated groups, nevertheless, were commonly recognised by both hosts ( Fig 5 , epitopes highlighted in pink), reinforcing the immunodominant nature of these regions of MOMP.…”
Section: Discussionmentioning
confidence: 95%
“…To support the likelihood of this explanation, our previous B-cell epitope mapping studies also show that different epitopes were recognised in koalas infected with different C . pecorum ompA genotypes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…membrane [13][14][15][16]. However, to date Chlamydia vaccine studies have focused primarily on female animal models, and indeed initial efforts to develop a MOMP-based vaccine for the koala have been successful in inducing a cell-mediated response, as well as a humoral immune response, in the female koala following subcutaneous (s.c.) vaccination [4][5][6][7]. Further, this prototype vaccine has been shown to be safe, while eliciting a strong immune responses in healthy females, without worsening clinical symptoms in already diseased animals [4].…”
Section: Introductionmentioning
confidence: 99%